Enantioselective Synthesis of N,S-Acetals by an Oxidative Pummerer Type Transformation Using Anionic Phase-Transfer Catalysis - Biswas, Souvagya (Angew Chem Int Ed Engl, 2017)
We report the first enantioselective oxidative Pummerer-type transformation using anionic phase-transfer catalysis, resulting in the formation of enantioenriched sulfur bearing heterocycles. This reaction includes the direct oxidation of sulfides to the thionium intermediate, followed by an asymmetric intramolecular nucleophilic addition to form the chiral cyclic N,S-acetals with moderate to high enantioselectivites. Deuterium labelling experiments were performed to identify the stereodiscrimination step of this process. Further analysis of the reaction transition states by means of multidimensional correlations and DFT computations highlight the existence of a set of weak noncovalent interactions between the catalyst and substrate that governed the enantioselectivity of the reaction.